Psychological aspects of rendering dental care to elderly and senile patients - N. S. Fedorova; R. A. Saleev; Yu. N. Urukov; G. T. Saleeva; Yu. L. Vasil'ev (LLC "Endo Press", 2019)
The article describes current issues related to the peculiarities of building relationships between health care workers and patients of elderly and old age in a dental medical organization.Purpose: Authorial comprehensive study related to the research characteristics of quality of life in elderly and senile patients.Methods: The methods of logical and statistical analysis were used while researching the question of measuring quality of life in elderly and senile patients.Results: The organization of psychological support for patients visiting medical organizations can improve the quality of medical care for elderly patients, improve their social well-being and improve their quality of life.Summary: Analysis of the psychological aspects of dental care for patients of elderly and senile age can improve the efficiency of medical dental care and improve the quality of life of the elderly.